A 5Y grade 460MPa high toughness rutile seamless flux-cored welding wire

By using a specific proportion core powder component in the welding material, it is made into a 5Y -level 460MPa high -tough golden stone seamless seamless core welding wire, which solves the problem that the existing technology cannot meet the performance requirements of the 5Y level 460MPa, and realizes the welding material. High -efficiency welding and stable performance.

CN115990728BActive Publication Date: 2025-01-28CHINA SHIPBUILDING INDUSTRY CORPORATION NO725 RESEARCH INSTITUTE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310112415.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-14
Publication Date
2025-01-28
Estimated Expiration
2043-02-14

AI Technical Summary

Technical Problem

There is no welding material in the prior art that can meet the performance requirements of 5Y grade 460MPa.

Method used

5Y -grade 460MPa high -tough golden stone seamless core welded wires made of low -carbon steel skin and drug core powder. The core powder includes golden redstone, potassium titanate sodium, magnesium powder, titanium iron, manganese silicon alloy, 锆 锆 采, 锆 锆 采, 锆 锆 采, 锆 锆 采 采 采 Elements such as alumina, quartz, sodium fluoride, rare earth iron alloy, nickel powder, and electrolytic metal manganese are controlled by controlling the content and combination of these ingredients, adjusting the melting point of welding slag and the stability of the arc, and improving the effect of spreading the weld and the effect of launching molding and mechanical science performance.

Benefits of technology

The full -term welding process of welding materials and the stability of the performance of the welding material, which meets the performance requirements of the 5Y -level 460MPa, has good cracking resistance, low diffusion hydrogen, and strong moisture resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004077290670000091
    Figure BDA0004077290670000091
  • Figure BDA0004077290670000101
    Figure BDA0004077290670000101
  • Figure BDA0004077290670000102
    Figure BDA0004077290670000102
Patent Text Reader

Abstract

The invention provides a 5Y-grade 460MPa high-toughness rutile seamless flux-cored welding wire, comprising a low-carbon steel outer skin and flux core powder. The flux core powder comprises, by mass percentage, 35%-40% of rutile, 2%-4% of potassium sodium titanate, 3%-5% of magnesium powder, 2%-3% of ferrotitanium, 4%-6% of manganese silicon alloy, 0.5%-1.5% of zircon sand, 1%-3% of aluminum oxide, 0.5%-2% of quartz, 2%-3% of sodium fluoride, 0.5%-2% of rare earth iron alloy, 6%-8% of nickel powder, 4%-6% of electrolytic metal manganese, and the balance is iron powder. The present invention controls the melting point of welding slag by controlling the content of quartz and alumina, thereby improving the forming effect of the weld, and simultaneously uses potassium sodium titanate and sodium fluoride to balance arc stability and arc stiffness, thereby ensuring good welding processability; under the action of a variety of alloy deoxidizers, the morphology of inclusions in the weld is improved while deoxidation is performed, thereby ensuring the stability of the mechanical properties of the deposited metal and the butt joint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of welding materials, and in particular to a 5Y-grade 460MPa high-toughness rutile seamless flux-cored welding wire. Background Art

[0002] At present, with the gradual deepening of my country's high-quality economic development, the modern shipbuilding industry has changed from labor-intensive to technology-intensive. Large container ships, offshore wind power installation ships and advanced marine equipment will become the focus of the development of the shipbuilding and marine engineering industries in the next ten years. The technological upgrading of the shipbuilding and marine engineering industries has greatly driven the demand for related supporting high-efficiency welding materials for advanced equipment.

[0003] Welding accounts for more than 40% of the total man-hours in shipbuilding. The application of efficient welding materials is of great significance for improving production efficiency, improving the construction environment and ensuring welding quality. 2 Gas shielded flux-cored welding wire is widely used in the field of shipbuilding and marine engineering due to its excellent all-position welding processability and good adaptability to automated welding. In addition to the advantages of seamless flux-cored welding wire, seamless flux-cored welding wire also has the following significant advantages: ① The cross-section is closed, the welding wire has no moisture absorption phenomenon, can stably achieve ultra-low diffusible hydrogen, and has low cold crack sensitivity; ② The surface of the welding wire can be copper-plated, the welding arc is stable, and the welding process performance is excellent; ③ The welding wire has good rigidity and stable wire feeding to ensure the quality of the weld. Based on the above advantages, seamless flux-cored welding wire has a very large technical advantage when used in high-strength steel welding.

[0004] In order to ensure the strength and rigidity requirements of the structure and meet the requirements of weight reduction, the application ratio of high-strength steel, especially thick steel, in the field of shipbuilding and offshore engineering has gradually increased, and correspondingly, higher requirements have been put forward for the low-temperature toughness of supporting welding materials. At present, some equipment construction has put forward the demand for 5Y-level welding materials. In the existing technology, there is no welding material that can meet the 5Y-level 460MPa performance requirements. Summary of the invention

[0005] The problem solved by the present invention is that in the prior art, there is no welding material that can meet the 5Y grade 460MPa performance requirement.

[0006] The invention discloses a 5Y-grade 460MPa high-toughness rutile seamless flux-cored welding wire, comprising a low-carbon steel outer skin and flux-cored powder. The flux-cored powder comprises, by mass percentage, 35%-40% of rutile, 2%-4% of potassium sodium titanate, 3%-5% of magnesium powder, 2%-3% of ferrotitanium, 4%-6% of manganese silicon alloy, 0.5%-1.5% of zircon sand, 1%-3% of aluminum oxide, 0.5%-2% of quartz, 2%-3% of sodium fluoride, 0.5%-2% of rare earth iron alloy, 6%-8% of nickel powder, 4%-6% of electrolytic metal manganese, and the balance is iron powder.

[0007] The melting point of the welding slag is controlled by controlling the content of quartz and alumina, and the spreading and forming effect of the weld is improved. At the same time, potassium sodium titanate and sodium fluoride are used to balance the arc stability and arc stiffness to ensure that the welding wire has good welding processability. Under appropriate process specifications, all-position welding can be achieved and the welding process is stable. Under the action of various alloy deoxidizers, the morphology of inclusions in the weld is improved while deoxidation, thereby ensuring the stability of the mechanical properties of the deposited metal and the butt joint, meeting the performance requirements of the classification society's 5Y grade 460MPa welding materials, with good crack resistance, low diffusible hydrogen, and strong moisture absorption resistance of the welding wire.

[0008] The seamless flux-cored welding wire adopts a titanium-type flux-cored welding wire slag system, wherein the TiO 2 As the main slag-forming agent, it has a high solidification temperature and can adjust the liquid slag to short slag, which is suitable for all-position welding. 2 It is also the main arc stabilizer. The addition amount of rutile is 35%-40%. When the addition amount of rutile is less than 35%, it is easy to have incomplete slag coverage, affecting the forming effect of the deposited metal. When the addition amount of rutile is higher than 40%, it is easy to increase the debris in the weld and affect the mechanical properties of the deposited metal.

[0009] Potassium sodium titanate mainly includes Na 2 O.K 2 O、TiO 2 , where Na 2 O and K 2 O can improve the stability of the welding arc and play a role in stabilizing the arc. At the same time, Na 2 O and K 2 O can also improve the slag surface tension, which is conducive to all-position welding; TiO 2 As Na 2 O and K 2 The addition amount of potassium sodium titanate is between 2% and 4%. An addition amount higher than 4% will result in excessive smoke and dust, while an addition amount lower than 2% will affect the stability of the arc and cause the welding performance of the welding wire to deteriorate.

[0010] Magnesium powder can improve the deoxidation ability of welding wire and thus improve the mechanical properties of weld metal. At the same time, the deoxidation products can play a role in adjusting welding processability, because the deoxidation products of magnesium powder almost all enter the slag, which can increase the melting point of the slag and make the welding wire suitable for all-position welding. The amount of magnesium powder added is controlled at 3%-5%. When the amount of magnesium powder added is less than 3%, the deoxidation is insufficient, which easily makes the oxygen content of the weld metal too high, affecting the mechanical properties of the weld; when the amount of magnesium powder added is higher than 5%, it will reduce the adaptability of vertical welding and overhead welding, and increase the difficulty of welding control.

[0011] Ti in ferrotitanium is used to deoxidize the weld. Due to the great affinity between Ti and oxygen, Ti in the weld is in the form of tiny oxide particles (TiO, Ti 2 O 3 、TiO 2 ) is dispersed in the weld and is very easy to become the nucleation core of acicular ferrite, which is conducive to the formation of acicular ferrite structure, thereby improving the toughness of the weld metal. The addition amount of ferrotitanium is 2%-3%. When the addition amount of ferrotitanium is less than 2%, the nucleation core of acicular ferrite is insufficient, resulting in insufficient acicular ferrite structure in the weld, affecting the low-temperature toughness of the deposited metal. When the addition amount of ferrotitanium is higher than 3%, the oxygen content in the molten pool will be too high, affecting the vertical welding and overhead welding.

[0012] Manganese silicon alloy includes Mn and Si, which are used for deoxidation of the liquid molten pool during welding to ensure that the weld metal has good performance. In addition, the deoxidation products of Mn and Si can adjust the fluidity of the liquid molten pool, thereby improving the welding processability of the welding wire. The addition amount of manganese silicon alloy is 4%-6%. When the addition amount is less than 4%, the improvement of deoxidation and welding processability is not good, and the performance of the weld metal is not good. When the addition amount is greater than 6%, excess Mn and Si will be transferred to the weld metal, resulting in a decrease in the toughness of the weld metal, especially the low-temperature toughness, which will be greatly reduced.

[0013] Zircon sand is mainly used to provide ZrO 2 To improve the slag removal performance of the weld, ZrO 2 It has a negative linear expansion coefficient and its volume changes during cooling, which has a positive effect on the smooth peeling of the slag shell. 2 As a high melting point material, it can adjust the viscosity of the slag pool, improve the weld formation, and ensure the processability of the weld. The addition amount of zircon sand is 0.5%-1.5%. When the addition amount is less than 0.5%, it is easy to be difficult to remove the slag. When the addition amount is higher than 1.5%, dense dot-shaped pits will form on the weld surface, affecting the weld formation.

[0014] Alumina is used to adjust the viscosity of slag, improve the fluidity and surface tension of liquid slag, and ensure the processability of welding wire in all positions. The addition amount of alumina is 1%-3%. When the addition amount is less than 1%, the viscosity of the slag is too high, which is not conducive to the deoxidation and forming of the weld. When the addition amount is higher than 3%, the viscosity will drop too much, causing the vertical welding pool to fall, affecting the processability of all-position welding.

[0015] The main component of quartz is SiO 2 Zircon sand can also provide some SiO 2 , SiO 2It is used to adjust the viscosity and fluidity of the liquid molten pool to ensure the processability of the welding wire. Considering the amount of zircon sand added, the amount of quartz added is 0.5%-2%. When the amount added is less than 1%, the slag viscosity is too high, which is not conducive to the deoxidation and forming of the weld. When the amount added is higher than 2%, the viscosity will drop too much, causing the vertical welding molten pool to fall, affecting the processability of all-position welding.

[0016] Sodium fluoride is used to increase the arc penetration so that the welding arc can obtain the appropriate penetration depth during welding. The addition amount of sodium fluoride is 2%-3%. When the addition amount is less than 2%, the arc penetration is insufficient and the penetration depth is insufficient during welding, which affects the welding efficiency and welding quality. When the addition amount is higher than 3%, it will affect the stability of the arc and affect the smooth progress of welding.

[0017] Rare earth iron alloys are used to improve the mechanical properties of weld metals. On the one hand, rare earth iron alloys deoxidize and desulfurize the weld through metallurgical action to purify the weld metal. On the other hand, the deoxidation products of rare earth iron alloys can spheroidize and refine the inclusions in the weld, promote the nucleation of acicular ferrite, and improve the low-temperature toughness of the weld. The addition amount of rare earth iron alloys is 0.5%-2%. When the addition amount is less than 0.5%, it is easy to cause the inclusion content in the weld to increase, which seriously affects the low-temperature impact toughness of the weld. When the addition amount is higher than 2%, too much rare earth elements will contaminate the grain boundaries of the weld, resulting in an increase in proeutectoid ferrite at the grain boundaries, thereby reducing the low-temperature impact toughness of the weld.

[0018] Nickel powder is used to improve the mechanical properties of weld metal. As an austenitizing element, nickel can promote the ductile-brittle transition temperature to move to the low temperature zone and improve the toughness of weld metal. The amount of nickel powder added is 6%-8%. When the amount added is less than 6%, the toughness of the weld metal is insufficient. When the amount added is higher than 8%, pores are likely to appear in the weld, affecting the mechanical properties of the weld metal.

[0019] The main purpose of electrolytic manganese is to introduce Mn elements as alloying agents to obtain the appropriate composition of the deposited metal, and then obtain the appropriate strength and toughness match. The addition amount of electrolytic manganese is 4%-6%. When the addition amount is less than 4%, it will affect the strength of the weld metal. When the addition amount is higher than 6%, the weld metal strength will be too high and the toughness will be reduced.

[0020] Furthermore, the rare earth iron alloy is at least one of rare earth calcium silicon and rare earth ferrosilicon.

[0021] Furthermore, in terms of mass percentage, the core powder includes 35% rutile, 4% potassium sodium titanate, 5% magnesium powder, 2% ferrotitanium, 4% manganese silicon alloy, 0.5% zircon sand, 2% alumina, 2% quartz, 3% sodium fluoride, 2% rare earth ferrosilicon, 8% nickel powder, 6% electrolytic manganese, and the balance is iron powder.

[0022] Furthermore, in terms of mass percentage, the core powder includes 38% rutile, 2% potassium sodium titanate, 3% magnesium powder, 3% ferrotitanium, 6% manganese silicon alloy, 1.5% zircon sand, 3% alumina, 1% quartz, 3% sodium fluoride, 2% rare earth silicon calcium, 6% nickel powder, 4% electrolytic manganese, and the balance is iron powder.

[0023] Furthermore, the core powder includes, by mass percentage, 40% rutile, 3% potassium sodium titanate, 4% magnesium powder, 2% ferrotitanium, 6% manganese silicon alloy, 1.5% zircon sand, 1% alumina, 0.5% quartz, 2% sodium fluoride, 0.5% rare earth ferrosilicon, 0.5% rare earth calcium silicon, 7% nickel powder, 4% electrolytic manganese, and the balance is iron powder.

[0024] Furthermore, the flux core powder accounts for 13%-16% of the total mass of the flux cored welding wire.

[0025] Furthermore, the diameter of the flux-cored welding wire is 1.2 mm.

[0026] Furthermore, in the potassium sodium titanate, TiO 2 ≥60%, K 2 O ≥ 20%, Na 2 O≥5%.

[0027] Furthermore, in the titanium iron, by mass percentage, 27%≤Ti≤32%.

[0028] Furthermore, in the silicon-manganese alloy, by mass percentage, 65%≤Mn≤72%, 14%≤Si≤17%, and C≤2.5%.

[0029] Compared with the prior art, the 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire of the present invention has the following advantages:

[0030] 1) The welding wire adopts a titanate slag system mainly composed of rutile. By controlling the content of quartz and alumina, the melting point of the slag can be properly controlled to improve the spreading and forming effect of the weld. At the same time, potassium sodium titanate and sodium fluoride are used to balance the arc stability and arc stiffness, ensuring that the welding wire has good processability. Under appropriate process specifications, all-position welding can be achieved and the welding process is stable;

[0031] 2) Under the action of various alloy deoxidizers, the weld metal composition is within a reasonable range, and rare earth iron alloy is added to the welding wire formula, which improves the morphology of inclusions in the weld while deoxidizing, thereby ensuring the stability of the mechanical properties of the deposited metal and the butt joint, meeting the performance requirements of the classification society's 5Y grade 460MPa welding materials, with good crack resistance, low diffusible hydrogen, and strong resistance to moisture absorption of the welding wire. DETAILED DESCRIPTION

[0032] To make the purpose, technical solutions and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with embodiments. It should be understood that the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.

[0033] A 5Y-grade 460MPa high-toughness rutile seamless flux-cored welding wire according to an embodiment of the present invention is described in detail below.

[0034] Example 1

[0035] The present embodiment provides a 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire, comprising a low-carbon steel sheath and flux-cored powder. The flux-cored powder comprises, by mass percentage, 35%-40% rutile, 2%-4% potassium sodium titanate, 3%-5% magnesium powder, 2%-3% ferrotitanium, 4%-6% manganese silicon alloy, 0.5%-1.5% zircon sand, 1%-3% alumina, 0.5%-2% quartz, 2%-3% sodium fluoride, 0.5%-2% rare earth iron alloy, 6%-8% nickel powder, 4%-6% electrolytic manganese, and the balance is iron powder.

[0036] In this embodiment, the melting point of the welding slag is controlled by controlling the content of quartz and alumina, thereby improving the spreading and forming effect of the weld. At the same time, potassium sodium titanate and sodium fluoride are used to balance the arc stability and arc stiffness to ensure that the welding wire has good welding processability. Under appropriate process specifications, all-position welding can be achieved and the welding process is stable. Under the action of a variety of alloy deoxidizers, the morphology of inclusions in the weld is improved while deoxidation is performed, thereby ensuring the stability of the mechanical properties of the deposited metal and the butt joint, meeting the performance requirements of the classification society's 5Y grade 460MPa welding materials, with good crack resistance, low diffusible hydrogen, and strong resistance to moisture absorption of the welding wire.

[0037] In this embodiment, the seamless flux-cored welding wire adopts a titanium-type flux-cored welding wire slag system, wherein the TiO 2 As the main slag-forming agent, it has a high solidification temperature and can adjust the liquid slag to short slag, which is suitable for all-position welding. 2 It is also the main arc stabilizer. The addition amount of rutile is 35%-40%. When the addition amount of rutile is less than 35%, it is easy to have incomplete slag coverage, affecting the forming effect of the deposited metal. When the addition amount of rutile is higher than 40%, it is easy to increase the debris in the weld and affect the mechanical properties of the deposited metal.

[0038] Potassium sodium titanate mainly includes Na 2 O.K 2 O、TiO 2, where Na 2 O and K 2 O can improve the stability of the welding arc and play a role in stabilizing the arc. At the same time, Na 2 O and K 2 O can also improve the slag surface tension, which is conducive to all-position welding; TiO 2 As Na 2 O and K 2 The addition amount of potassium sodium titanate is between 2% and 4%. An addition amount higher than 4% will result in excessive smoke and dust, while an addition amount lower than 2% will affect the stability of the arc and cause the welding performance of the welding wire to deteriorate.

[0039] Magnesium powder can improve the deoxidation ability of welding wire and thus improve the mechanical properties of weld metal. At the same time, the deoxidation products can play a role in adjusting welding processability, because the deoxidation products of magnesium powder almost all enter the slag, which can increase the melting point of the slag and make the welding wire suitable for all-position welding. The amount of magnesium powder added is controlled at 3%-5%. When the amount of magnesium powder added is less than 3%, the deoxidation is insufficient, which easily makes the oxygen content of the weld metal too high, affecting the mechanical properties of the weld; when the amount of magnesium powder added is higher than 5%, it will reduce the adaptability of vertical welding and overhead welding, and increase the difficulty of welding control.

[0040] Ti in ferrotitanium is used to deoxidize the weld. Due to the great affinity between Ti and oxygen, Ti in the weld is in the form of tiny oxide particles (TiO, Ti 2 O 3 、TiO 2 ) is dispersed in the weld and is very easy to become the nucleation core of acicular ferrite, which is conducive to the formation of acicular ferrite structure, thereby improving the toughness of the weld metal. The addition amount of ferrotitanium is 2%-3%. When the addition amount of ferrotitanium is less than 2%, the nucleation core of acicular ferrite is insufficient, resulting in insufficient acicular ferrite structure in the weld, affecting the low-temperature toughness of the deposited metal. When the addition amount of ferrotitanium is higher than 3%, the oxygen content in the molten pool will be too high, affecting the vertical welding and overhead welding.

[0041] Manganese silicon alloy includes Mn and Si, which are used for deoxidation of the liquid molten pool during welding to ensure that the weld metal obtains good performance. In addition, the deoxidation products of Mn and Si can adjust the fluidity of the liquid molten pool, thereby improving the welding processability of the welding wire. The addition amount of manganese silicon alloy is 4%-6%. When the addition amount is less than 4%, the improvement of deoxidation and welding processability is not good, and the performance of the weld metal is not good. When the addition amount is greater than 6%, excess Mn and Si will be transferred to the weld metal, resulting in a decrease in the toughness of the weld metal, especially the low-temperature toughness, which will be greatly reduced. In this application, manganese silicon alloy, titanium iron, etc. are used as alloy deoxidizers to effectively reduce the oxygen content in the deposited metal.

[0042] Zircon sand is mainly used to provide ZrO2 To improve the slag removal performance of the weld, ZrO 2 It has a negative linear expansion coefficient and its volume changes during cooling, which has a positive effect on the smooth peeling of the slag shell. 2 As a high melting point material, it can adjust the viscosity of the slag pool, improve the weld formation, and ensure the processability of the weld. The addition amount of zircon sand is 0.5%-1.5%. When the addition amount is less than 0.5%, it is easy to be difficult to remove the slag. When the addition amount is higher than 1.5%, dense dot-shaped pits will form on the weld surface, affecting the weld formation.

[0043] Alumina is used to adjust the viscosity of slag, improve the fluidity and surface tension of liquid slag, and ensure the processability of welding wire in all positions. The addition amount of alumina is 1%-3%. When the addition amount is less than 1%, the viscosity of the slag is too high, which is not conducive to the deoxidation and forming of the weld. When the addition amount is higher than 3%, the viscosity will drop too much, causing the vertical welding pool to fall, affecting the processability of all-position welding.

[0044] The main component of quartz is SiO 2 Zircon sand can also provide some SiO 2 , SiO 2 It is used to adjust the viscosity and fluidity of the liquid molten pool to ensure the processability of the welding wire. Considering the amount of zircon sand added, the amount of quartz added is 0.5%-2%. When the amount added is less than 1%, the slag viscosity is too high, which is not conducive to the deoxidation and forming of the weld. When the amount added is higher than 2%, the viscosity will drop too much, causing the vertical welding molten pool to fall, affecting the processability of all-position welding.

[0045] Sodium fluoride is used to increase the arc penetration so that the welding arc can obtain the appropriate penetration depth during welding. The addition amount of sodium fluoride is 2%-3%. When the addition amount is less than 2%, the arc penetration is insufficient and the penetration depth is insufficient during welding, which affects the welding efficiency and welding quality. When the addition amount is higher than 3%, it will affect the stability of the arc and affect the smooth progress of welding.

[0046] Rare earth iron alloys are used to improve the mechanical properties of weld metals. On the one hand, rare earth iron alloys deoxidize and desulfurize the weld through metallurgical action to purify the weld metal. On the other hand, the deoxidation products of rare earth iron alloys can spheroidize and refine the inclusions in the weld, promote the nucleation of acicular ferrite, and improve the low-temperature toughness of the weld. The addition amount of rare earth iron alloys is 0.5%-2%. When the addition amount is less than 0.5%, it is easy to cause the inclusion content in the weld to increase, which seriously affects the low-temperature impact toughness of the weld. When the addition amount is higher than 2%, too much rare earth elements will contaminate the grain boundaries of the weld, resulting in an increase in proeutectoid ferrite at the grain boundaries, thereby reducing the low-temperature impact toughness of the weld.

[0047] Nickel powder is used to improve the mechanical properties of weld metal. As an austenitizing element, nickel can promote the ductile-brittle transition temperature to move to the low temperature zone and improve the toughness of weld metal. The amount of nickel powder added is 6%-8%. When the amount added is less than 6%, the toughness of the weld metal is insufficient. When the amount added is higher than 8%, pores are likely to appear in the weld, affecting the mechanical properties of the weld metal.

[0048] The main purpose of electrolytic manganese is to introduce Mn elements as alloying agents to obtain the appropriate composition of the deposited metal, and then obtain the appropriate strength and toughness match. The addition amount of electrolytic manganese is 4%-6%. When the addition amount is less than 4%, it will affect the strength of the weld metal. When the addition amount is higher than 6%, the weld metal strength will be too high and the toughness will be reduced.

[0049] The flux core powder accounts for 13%-16% of the total mass of the flux cored welding wire.

[0050] The diameter of the flux-cored welding wire is 1.2 mm.

[0051] The rare earth iron alloy is at least one of rare earth calcium silicon and rare earth ferrosilicon.

[0052] In this embodiment, the particle size of each component of the core powder is 80 mesh and all pass through.

[0053] In this embodiment, the preparation process of the seamless flux-cored welding wire includes: adding flux-cored powder online synchronously, rolling and welding the outer steel strip after adding the flux-cored powder, and then annealing, reducing the diameter and copper plating to prepare the seamless flux-cored welding wire. The specific preparation method can be referred to Chinese patent CN201110266933.1, which will not be described in detail here.

[0054] The component requirements of each raw material in the above-mentioned core powder are shown in Table 1.

[0055] Table 1 Requirements for the components of the main raw materials

[0056]

[0057] Example 2

[0058] This embodiment provides a 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire. According to the components of the flux-cored powder described in Example 1, three kinds of flux-cored powder materials are configured, and low-carbon steel strip is used as the outer skin of the welding wire to prepare three kinds of seamless flux-cored welding wires, which are marked as T1, T2, and T3 respectively, and the diameter of the welding wire is Φ1.2mm. The specific mass ratio of the flux-cored powder in each flux-cored welding wire is shown in Table 1, and the welding wire filling rate (i.e., the percentage of the flux-cored powder in the total mass of the flux-cored welding wire) is shown in Table 2. The shielding gas used in the welding of the three seamless flux-cored welding wires is carbon dioxide.

[0059] Table 1 Composition of flux core powder of T1, T2 and T3 seamless flux cored wires in this embodiment (wt%)

[0060]

[0061]

[0062] Table 2 Filling rate of core powder of seamless flux-cored welding wire in this embodiment (%)

[0063]

[0064] The chemical composition and properties of the low carbon steel strip used to prepare the flux-cored welding wire in this embodiment are shown in Table 3 and Table 4 respectively.

[0065] Table 3 Chemical composition (wt%) of the steel strip used for the seamless flux-cored welding wire in this embodiment

[0066] chemical composition C Si Mn S P Fe content 0.033 0.02 0.21 0.005 0.01 margin

[0067] Table 4 Performance of the steel strip selected for the seamless flux-cored welding wire in this embodiment

[0068]

[0069] The chemical composition and mechanical properties of the deposited metals of the three seamless flux-cored welding wires T1, T2 and T3 in this embodiment are shown in Tables 5 and 6.

[0070] Table 5 Chemical composition of the deposited metal of the seamless flux-cored welding wire in this embodiment (wt%)

[0071]

[0072]

[0073] Table 6 Mechanical properties of the deposited metal of the seamless flux-cored welding wire in this embodiment

[0074]

[0075] CCS (China Classification Society) has the following mechanical property requirements for the deposited metal of 5Y grade 460MPa welding materials: yield strength ≥460MPa, tensile strength 540-720MPa, elongation ≥20%, KV 2(-60℃) ≥47J, it can be seen that the three seamless flux-cored welding wires T1, T2 and T3 provided in this embodiment can meet the requirements of CCS classification society for 5Y grade 460MPa welding materials, and the deposited metals thereof have excellent low-temperature impact toughness.

[0076] It should be noted that all the terms used in the present invention to indicate directionality and position, such as "upper", "lower", "left", "right", "front", "back", "vertical", "horizontal", "inner", "outer", "top", "lower", "tail end", "head end", "center", etc., are only used to explain the relative positional relationship and connection status between the components in a certain state, and are only for the convenience of describing the present invention, rather than requiring the present invention to be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the descriptions of "first", "second", etc. in the present invention are only used for descriptive purposes, and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.

[0077] Although the present invention is disclosed as above, the present invention is not limited thereto. Any person skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the scope defined by the claims.

Claims

1. A 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire, comprising a low-carbon steel sheath and a flux core powder, characterized in that: The core powder comprises, by mass percentage, 35%-40% rutile, 2%-4% potassium sodium titanate, 3%-5% magnesium powder, 2%-3% ferrotitanium, 4%-6% manganese silicon alloy, 0.5%-1.5% zircon sand, 1%-3% alumina, 0.5%-2% quartz, 2%-3% sodium fluoride, 0.5%-2% rare earth iron alloy, 6%-8% nickel powder, 4%-6% electrolytic manganese, and the remainder is iron powder, wherein, in the potassium sodium titanate, by mass percentage, TiO2≥60%, K2O≥20%, and Na2O≥5%; in the ferrotitanium, by mass percentage, 27%≤Ti≤32%.

2. The 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire according to claim 1, characterized in that: The rare earth iron alloy is at least one of rare earth calcium silicon and rare earth ferrosilicon.

3. The 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire according to claim 2, characterized in that: Calculated by mass percentage, the core powder includes 35% rutile, 4% potassium sodium titanate, 5% magnesium powder, 2% ferrotitanium, 4% manganese silicon alloy, 0.5% zircon sand, 2% alumina, 2% quartz, 3% sodium fluoride, 2% rare earth ferrosilicon, 8% nickel powder, 6% electrolytic manganese, and the balance is iron powder.

4. The 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire according to claim 2, characterized in that: Calculated by mass percentage, the core powder includes 38% rutile, 2% potassium sodium titanate, 3% magnesium powder, 3% ferrotitanium, 6% manganese silicon alloy, 1.5% zircon sand, 3% alumina, 1% quartz, 3% sodium fluoride, 2% rare earth silicon calcium, 6% nickel powder, 4% electrolytic manganese, and the balance is iron powder.

5. The 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire according to claim 2, characterized in that: Calculated by mass percentage, the core powder includes 40% rutile, 3% potassium sodium titanate, 4% magnesium powder, 2% ferrotitanium, 6% manganese silicon alloy, 1.5% zircon sand, 1% alumina, 0.5% quartz, 2% sodium fluoride, 0.5% rare earth ferrosilicon, 0.5% rare earth calcium silicon, 7% nickel powder, 4% electrolytic manganese, and the balance is iron powder.

6. A 5Y grade 460MPa high toughness rutile seamless flux-cored welding wire as claimed in claim 1, characterized in that: The flux core powder accounts for 13%-16% of the total mass of the flux cored welding wire.

7. A 5Y grade 460MPa high-toughness rutile seamless flux-cored welding wire as claimed in claim 1, characterized in that: The diameter of the flux-cored welding wire is 1.2 mm.

8. A 5Y grade 460MPa high toughness rutile seamless flux-cored welding wire as claimed in claim 1, characterized in that: In the manganese silicon alloy, by mass percentage, 65%≤Mn≤72%, 14%≤Si≤17%, and C≤2.5%.

Citation Information

Patent Citations

  • Manufacturing method of seamless flux-cored wire

    CN102310302A

  • Low-hydrogen high-toughness seamless flux-cored wire for low-temperature steel and preparation method of low-hydrogen high-toughness seamless flux-cored wire

    CN109623193A